Total Synthesis of Chaetoglobin A via Catalytic, Atroposelective Oxidative Phenol Coupling - Kang, Houng (Org Lett, 2018)
The first total synthesis of chaetoglobin A (1), which features a chiral axis between two identical highly oxygenated bicyclic cores, was successfully completed in 12 steps from 2,6-dimethoxytoluene. Vanadium-catalyzed oxidative phenol coupling, as a key step, enabled generation of the axial chirality.